A Driving Simulation Study Examining Destination Entry with iOS 5 Google Maps and a Garmin Portable GPS System. (September 2013) - Dopart, Celena; Häggman, Anders; Thornberry, Cameron; Mehler, Bruce; Dobres, Jonathan; Reimer, Bryan
A simulation study compared 23 young adult drivers' task completion time, mean glance time, number of glances, and percentage of long glances while performing a navigation entry task with a Garmin portable GPS system and a mobile navigation application (iOS 5 Google Maps) on an iPod Touch. We compared participants' performance on these tasks using the National Highway Traffic Safety Administration (NHTSA) eye-glance acceptance criteria. We found that, irrespective of the device used, no participant was able to complete the task within the recommended total time window of 12 seconds. When entering a destination into the iOS interface, only 73.9% of the drivers meet the NHTSA criteria for long duration glances. With the Garmin system, 91.3% of the participants meet this criterion. All participants were able to maintain adequate mean off road glance durations. Finally, we compared the NHTSA recommended method of assessing all off road glances to more traditional methods of assessing glances only to the task interface. Differences between the two methods are discussed.